Ad Hoc Networks 7th International Conference, AdHocHets 2015, San Remo, Italy, September 1-2, 2015. Proceedings - Mitton, Nathalie; Kantarci, Melike Erol; Gallais, Antoine; Papavassiliou, Symeon (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2015)
This book constitutes the proceedings of the International Conference on Ad Hoc Networks, ADHOCNETS 2015, held in September 2015 in Italy. The 17 regular and 3 invited papers presented were carefully reviewed and selected from numerous submissions. The papers cover topics such as physical layer; MAC and routing; mobility in networks; self-organization, virtualization and localization; cloud, virtualization and prototypage; security and fault tolerance in wireless mobile networks.